Determinants of Community Consensus in Small Scale Hydropower Development Project: A Case Study of Bhujung Hydropower Project - Ojha , Rajendra (Nepalese Journal of Management Science and Research, 2023)
This research highlights the issues, negotiation and consensus process of a local community confrontations with the commercial as well as development projects that are to be started in a particular location, especially in the places where there are lots of conflicts and misunderstanding between project holders, development entrepreneurs and local communities. This research is based on a case study of the 7.5 MW 'Bhujung Hydropower Project' located at Lamjung district, Gandaki province of Nepal. Data collected through primary survey, focus group discussion and personal interviews of purposively contacted samples are deeply analyzed applying qualitative, descriptive and narrative methods. This study result shows that it is necessary to pre-allocate the budget that would be necessary in the future to develop secondary mini-project for local community beneficiary development activities of that community to address issues based on economic development that would arise during FGD period in order to execute primary entrepreneurial or development projects properly through consensus. This study concludes that the best strategy to execute community consensus in the society by any development or entrepreneurial project based organizations is to look after basic community needs as well as factors influencing the path of community consensus while undertaking any project based developmental activities.